Penerapan Business Model Canvas dalam Meningkatkan Daya Saing Produk PT Jamkrindo Syariah Purwokerto - Lili Erlina; Hasnita, Yuliana Nur; Cahyani, Agustin Tri; Shafrani, Yoiz Shofwa (FEB Universitas Maritim Semarang, 2025)
This study aims to analyze the implementation of the Business Model Canvas (BMC) at the Purwokerto branch of PT Jamkrindo Syariah in addressing competitiveness within the Islamic finance sector. The BMC is a strategic framework consisting of nine building blocks: customer segments, value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partnerships, and cost structure. This research employs a qualitative approach with descriptive analysis, utilizing observation and unstructured interviews with relevant stakeholders as data collection techniques. The findings reveal that the application of BMC at PT Jamkrindo Syariah has been optimal and has positively impacted the company’s operations, particularly in market penetration, customer relationship management, and cost efficiency. Furthermore, partnerships with both private and governmental institutions serve as critical elements for ensuring business sustainability. The study recommends that the company continuously pursue product innovation, strengthen digital channels, enhance human resources, and regularly evaluate its business model to remain responsive to market changes. Effective implementation of BMC can serve as a strategic tool to boost the company’s competitive advantage.